Type the answers in the spaces provided. Use numbers instead of words. Determine the solution to the linear system by using the substitution method. \( \left\{\begin{array}{l}y=4 x+2 \\ y=3 x-2\end{array}\right. \) Answer Determine the solution to the linear system by using the substitution method. \( \left\{\begin{array}{l}3 x+2 y=4 \\ 2 x-y=5\end{array}\right. \) Answer (
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the first linear system using substitution, we can set the equations equal to each other since they both equal y: 1. \( 4x + 2 = 3x - 2 \) Subtract \( 3x \) from both sides: 2. \( 4x - 3x + 2 = -2 \) This simplifies to: 3. \( x + 2 = -2 \) Now, subtract 2 from both sides: 4. \( x = -4 \) Using the value of x in one of the equations to find y, we'll use \( y = 4x + 2 \): 5. \( y = 4(-4) + 2 \) 6. \( y = -16 + 2 = -14 \) So the solution to the first system is: \( (-4, -14) \) --- Now for the second system, we start with the first equation \( 3x + 2y = 4 \). We can isolate y: 1. \( 2y = 4 - 3x \) 2. \( y = \frac{4 - 3x}{2} \) Now we'll substitute this expression for y in the second equation \( 2x - y = 5 \): 3. \( 2x - \frac{4 - 3x}{2} = 5 \) To eliminate the fraction, multiply everything by 2: 4. \( 4x - (4 - 3x) = 10 \) 5. \( 4x - 4 + 3x = 10 \) Combining like terms gives us: 6. \( 7x - 4 = 10 \) Adding 4 to both sides: 7. \( 7x = 14 \) Dividing by 7: 8. \( x = 2 \) Now we substitute back to find y using \( y = \frac{4 - 3x}{2} \): 9. \( y = \frac{4 - 3(2)}{2} \) This simplifies to: 10. \( y = \frac{4 - 6}{2} = \frac{-2}{2} = -1 \) So the solution to the second system is: \( (2, -1) \)